Implementation of Warehouse Receipt System in Food Warehouses in Kudus District - Faza, Iqbal; Sekarningtyas, Hikmah; Arti, Titi Yuni; Noviana, Eka (Jurnal Logistik Indonesia, 2023)
Agriculture is a sector that is able to score growth during the pandemic crisis. The export performance of the agricultural sector also continues to show positive growth. For this reason, real support is needed so that agriculture can continue to grow sustainably. One of them is by building a modern agricultural commodity product storage system, one of which is by using a warehouse receipt system. The warehouse receipt system has very strategic functions, including as a stock management instrument, logistics financing instrument, and supporting food security efforts. Unfortunately, the utilization of the warehouse receipt system in Kudus Regency is still very low, as indicated by the minimal utilization of the warehouse receipt system. This research aims to analyze the reasons why the warehouse receipt system has not been optimally utilized by farmers. This research uses a qualitative method with Miles and Huberman's interactive data analysis, namely: data collection, data reduction, data display, and conclusion drawing/verification. The results of this study indicate that SRG has great potential to improve the welfare of farmers and advance the agricultural sector in Kudus Regency. However, to overcome various obstacles that hinder the implementation of SRG, serious efforts are needed from various parties, namely: Increase public knowledge and awareness about SRG; simplify the process and requirements for using SRG; improve SRG infrastructure, including information systems and warehouses; improve the ability of farmers to obtain financing through SRG; and improve cooperation between related agencies.